(3hbGjI GdQhGjIs - (3UOQ GdTQjYIs
(3ChdgG (B:s
(3YfO CHj MfjaI QMeI QDjI GdeJjee GdeGA hfRY GdeGSHM VaI HYed jSjQ s
(3BNQgG (B:s
(3jfJgi HcJGH GdNfKi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfajs